Audience's Perception of the Impact of Social Media on Film “The Social Dilemma” - Fajrin, Sadiah; Siregar, Yusra Dewi; Monang, Sori (Pena Cendekia Insani, 2022)
This article or writing aims to find out what kind of perception arises in the audience regarding the issue of the impact of social media that is shown in the film The Social Dilemma. The problem is focused on the type of perception that comes out when watching the film The Social Dilemma, whether the perception is positive or negative. Marshal McLuhan, The data were collected through Questionnaire and Literature Study and analyzed quantitatively. This study concludes that 57.7% of respondents answered that the message conveyed was related to the impact of social media, which means that the perception that arises is a positive perception after the audience watches the film The Social Dilemma.